2015
DOI: 10.1364/ao.54.009573
|View full text |Cite
|
Sign up to set email alerts
|

3D mouse shape reconstruction based on phase-shifting algorithm for fluorescence molecular tomography imaging system

Abstract: We introduce a fast, low cost, and robust method, based on fringe pattern and phase shifting, to obtain three-dimensional (3D) mouse surface geometry for fluorescence molecular tomography (FMT) imaging. We use two pairs of pico-projector and webcam to project and capture fringe patterns from different views. At first, we calibrate the pico-projectors and the webcams to obtain their system parameters. Each pair of pico-projector and webcam has its own coordinate system. We use a cylindrical calibration bar to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…1. 10 Two pairs of pico-projector and webcam were used to measure the object surface from two different views. After the surface was measured, the object was moved into the conical mirror by a linear stage for FMT scan.…”
Section: Conical Mirror Based Fmt Imaging Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…1. 10 Two pairs of pico-projector and webcam were used to measure the object surface from two different views. After the surface was measured, the object was moved into the conical mirror by a linear stage for FMT scan.…”
Section: Conical Mirror Based Fmt Imaging Systemmentioning
confidence: 99%
“…The details of the calibration and node-to-pixel mapping of this system can be found in Ref. 10. And the reconstruction algorithms that were applied to this study can be found in Refs.…”
Section: Conical Mirror Based Fmt Imaging Systemmentioning
confidence: 99%